The Virginia Tech Shooting : News Values and Critical Analysis of News Discourse in Online News Articles - Peltomaa, Heidi (fi=Turun yliopisto|en=University of Turku|, 2017)
The Virginia Tech shooting incident, which took place in 2007 in the state of Virginia in the United States, was the largest mass shooting in the history of the country. The incident was reported all around the world and covered by numerous news organisations, including the two large U.S. news organisations, namely, The New York Times and The Washington Post. The aim of my research is, firstly, to analyse in total six online news articles from the websites of The New York Times and The Washington Post in order to determine what news values can be attached to the incident and how it became news; and secondly, to analyse these articles critically in order to gain knowledge about the perceived objectivity of the writers of these news articles as well as the organisations they work for. The framework that is used in the analysis of the news articles combines features from fields of discourse analysis, critical discourse analysis (CDA) and critical linguistics. The linguistic devices used in the analysis are lexical analysis and sentence construction. Lexical analysis focuses on the vocabulary and choice of words, while sentence construction focuses on the syntactic concepts of nominalisation and passivisation as well as modality. The results of the study showed that the Virginia Tech shooting became news because it filled a number of news criteria, which made the incident more newsworthy. The critical linguistic analysis of the news articles showed that the incident was objectively reported on by the writers and news organisations. However, in some instances, the objective stance of the writer could be called into question.